Analysis for the heat transfer of fully tempered vacuum glazing based on the thermal resistance model and finite element model. (September 2018) - Hu, Dongfang; Li, Yichen; Liu, Chang; Li, Yanbing
The fully tempered vacuum glazing, consisting of two fully tempered glass plates detached through a limited vacuum medium (below 0.01 Pa), is presented. The heat transfer through fully tempered vacuum glazing is complex, including heat conduction, thermal radiation, and convection. To analyze heat conduction through a stainless steel support ball, the thermal resistance of the support ball is established based on Hertzian contact model. And the total thermal resistance of the unit cell with one support ball is defined. The three-dimensional finite element model for a center unit cell of fully tempered vacuum glazing is simulated to validate the result of the total thermal resistance. The simulation transmission U-values are 0.26 W/m 2 K. Meanwhile, the simulation transmission U-values of entire fully tempered vacuum glazing are 0.84 W/m 2 K without frame insulation.